Africa Diary: News from the continent 1 June – 31 August 2025 - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2025)
A selection of events about, and from across, the continent that are significant or interesting, or both. Compiled by the New Agenda Editorial Collective at the Institute for African Alternatives, we welcome contributions for ideas on what to include.